Emergent climate protection strategies in German hospitals: A cluster analysis. - Lara Schmidt; Sabine Bohnet-Joschko (PLoS ONE)
Hospitals emit large amounts of greenhouse gas emissions during healthcare delivery due to their extensive resource utilization and substantial waste generation. By implementing climate actions, hospitals can significantly contribute to climate protection in healthcare. This paper delves into the climate protection efforts of German hospitals, with a specific focus on the emergent strategies of hospital administrative leaders and the employee engagement within the framework of Stakeholder Theory. The investigation is based on primary data from an online survey of hospital administrative leaders in German hospitals. Employing a hierarchical cluster analysis, the study identifies four distinct clusters of hospitals. These clusters vary significantly in their organization and communication strategies regarding climate protection and allocation of responsibilities, indicating that German hospitals prioritize climate protection to varying degrees. The findings suggest that employee engagement depends on how hospital administrative leaders organize and communicate the topic of climate protection in their institutions. The study underscores the importance of strategic leadership for climate protection in hospitals.